Saturday

April 19, 2014

April 19, 2014

Posted by **Sabrina** on Friday, September 24, 2010 at 10:36pm.

(1-i33)/2

change it to the standard form first

x^2 - x + 7 = 0

a=1, b=-1, c = 7

x = (1 } (1 - 4(1)(7))/2

= (1 } -27)/2

Your answer is an imaginary number or called a complex number, you could rewrite is as

x = (1 } 33 i)/2

**Related Questions**

Math clarification Reiny - This is the problem you helped me with. I was curious...

RADICAL EXPRESSIONS/ALGEBRA 2 - Hi. I pretty much have the answer for these ...

Physics - If I have a diagram of Kepler's laws of planetary motion and it shows ...

Physics-Please check - If I have a diagram of Kepler's laws of planetary motion ...

trigonometry - tan 30degrees = sin 60degrees /1+cos 60degrees I pluged in the ...

Chemistry - Sulfite (SO3^2-) in wine was measured by the following procedure: 50...

Chemisry - The amount of I3(aq) in a solution can be determined by titration ...

Algebra 1 - Can you let me know if this answer is right. (22-43)(43)+83...

Calculus - 27 + 12 - 32 - 8 27 = 3*3*3 = 33 12 = 2*2*3 = 23...

Algebra - 1. Evaluate each. Write the answer in simplified radical form: __ __ ...